Counseling about cancer : strategies for genetic counseling - Schneider, Katherine A.; Chittenden, Anu; Shannon, Kristen Mahoney (Wiley-Blackwell, 2023)
Counseling About Cancer A key resource for all genetic counselors and other healthcare providers, this comprehensive reference has been completely updated and reorganized for its fourth edition Over 50 hereditary cancer predisposition genes have now been identified. Genetic testing can be a powerful tool in assessing individual cancer risk and creating robust medical plans, but can also be a complex process, with personal and familial factors carrying real emotional weight. As such, genetic counseling for patients and their families during the process of genetic testing is critical. Counseling about Cancer: Strategies for Genetic Counseling is the only comprehensive resource available for clinicians who want to understand and apply these dimensions of patient care. This updated and reorganized edition provides detailed information designed to be incorporated in a variety of clinical and health-care contexts. Updated with the latest guidance and research, it promises to continue as the indispensable guide to this challenging subject. Readers of the fourth edition of Counseling about Cancer will also find: * New chapters analyzing pediatric cancer syndromes, genetic testing technology, and more * Increased focus on gynecological cancer syndromes and related genes * Detailed case studies to reinforce themes of each chapter Counseling about Cancer is a useful reference for genetic counselors and other healthcare providers looking to familiarize themselves with best practices of patient counseling and care.